Brand transitioning : the transition to umbrella branding - Loh, Chor Hong (2015)
One of the popular catch phrases of the 1990's is "Globalisation". The Scott Paper Company, has been swept up by this infectious trend and gone global. For the Scott Paper Company, globalisation is approached through global umbrella branding. It decided in 1992 to undertake a global umbrella branding strategy and transition all its strategic individual brands into two main umbrella brands, namely, "Scottex" and "Cottonelle". The former is targeted at the "Mainstream Value segment" while the latter is targeted at the "Premium segment". Scott Paper Singapore (SPS) was saddled with the task of being the lead market in the transitioning of its individual brands to the two umbrella brands. The objective of this study is to examine and determine the resultant impact of Scott Paper Company's global brand transition in Scott Paper Singapore (SPS), on its brands, market performance and internal organisation impact and upheavals. Ultimately the questions: "Does the new strategy pay off?" and "Does the continuation of a global umbrella branding strategy make sense for Scott Paper?" will be answered. From our evaluation of SPS, the findings indicate that the new umbrella branding strategy had resulted in a greatly improved overall financial performance. Results show near doubling of sales volumes, market shares and profitability plus increases in its return on investment and a positive EVA (Economic Value Added). However, the greatest contributor to these results was the Scottex brand with its tremendous market performance and increased brand equity. Cottonelle is a totally different story with its drastic lost in market share and weakened brand equity compared to its previous individual brands. These great disparities in brand performance has provided lessons to be learnt in implementation of the transitioning process and in the umbrella branding strategy. The impact on the internal organisation examined through the 7-S framework. Corporate wide indications are for greater coordination between subsidiaries and a trend towards greater centralization through regionalisation. SPS's senior management also capitalised on the momentum of the upheaval to change the mind-sets of the SPS's employees to a more market-driven one. Additional skills and staff were added, especially in marketing and a learning culture has developed. All the elements of the framework examined showed an increasing "fit" with the branding strategy and the new strategy of being more market driven . The result is a healthier organisation overall. In conclusion, SPS was found to have profited from the new umbrella branding strategy and lessons learnt at SPS should be transferred to the other markets to ensure a smoother brand transition. However, the key success factors that were identified for SPS are probably only applicable to the Asia Pacific Region . Singapore, being one of the more sophisticated consumer markets with more demanding consumers in the region is the appropriate choice as the lead country for the region . Its success can hence be emulated to the other countries in this region . In view of this, the transferability of the above success to other markets in other regions like the US and EU, however, will be limited . To further determine the probability of success, we have examined the industry's potential for globalisation. As we used a broadbrush analysis of the industry, general conclusions were made with caution. We have found that in general , the sanitary tissue product industry is structurally attractive and should not be much of a impediment for Scott Paper to pursue a global strategy. A greater length of time is required for us to determine the full impact of the strategic change, presently, indications are that the strategy has paid off and Scott Paper should continue experimenting with the branding strategy in its other markets, especially the Pacific Region.